Part of your world : a twisted tale graphic novel - Strohm, Stephanie Kate (Twisted tale graphic novel., 2023)
Five years after the infamous sea witch defeated the little mermaid, Ariel--now the voiceless queen of Atlantica--must confront Ursula to restore justice on both land and sea, find her father, and reclaim Prince Eric's affections.